Rethinking EFL Grammar Instruction: Enhancing Student Outcomes through Self-Assessment in EFL Classrooms - Thamrin, Nur Sehang; Maf'ulah, Maf'ulah; Nadrun, Nadrun; Maghfira, Maghfira; Rusdi, Magfirah (Elsya : Journal of English Language Studies, 2025)
Mastery of grammar, particularly subject-verb agreement in the simple present tense, remains a persistent challenge for Indonesian EFL learners due to structural differences between English and Bahasa Indonesia. Traditional methods often fail to foster deep grammatical competence. In response, this study explores the effectiveness of integrating self-assessment (SA)  as a reflective learning strategy to enhance grammatical accuracy. Employing a quasi-experimental design, this study involved 38 third-semester English education students at a public university in Central Sulawesi, Indonesia. Participants were divided into an experimental group (n=18) that received SA-integrated grammar instruction and a control group (n=20) that received conventional instruction. Over eight sessions, students in the experimental group engaged SA activities using SA guidelines and reflection tasks while learning subject-verb agreement in the simple present tense. Pre- and post-tests were administered, and data were analyzed using descriptive statistics and independent sample t-tests.  The findings revealed that the experimental group's learning achievement outperforms its counterpart, with mean post-test scores of 17.17 and 13.15, respectively. The T-test results confirmed a statistically significant difference in grammar achievement between the groups (p<0.001), favoring the SA-integrated instruction. These findings suggest that SA is an effective strategy for improving student grammar outcomes in using subject-verb agreement correctly This study underscores the value of SA as a practical and impactful approach in EFL grammar instruction and supports its integration into learner-centered curricula, particularly in alignment with Indonesia’ Kurikulum Merdeka.